Efektivitas Layanan Self- Servise Bahan Bakar SPBU Stasiun Pertamina Mengunakan Analisias Blbliometrik - Misnah Azhari, Nur; Suratman, Suratman; Susanti, Is (Iapa Proceedings Conference, 2024)
This research examines the effectiveness of fuel self-service at SPBU Pertamina Station Rawa Makmur, Bengkulu City, using bibliometric analysis. Self-service is designed to improve efficiency and customer satisfaction in the refuelling process. Through bibliometric analysis, this research identifies current research trends and evaluation results from studies related to the implementation of self-service technology. Data were obtained from scientific publications, industry reports, and case studies. Results show that self-service implementation can reduce waiting time and increase customer satisfaction, although challenges such as technology adaptation and user training need to be addressed. The findings provide valuable insights for service development in the fuel industry, especially in the local context. This research is expected to guide service improvement strategies in petrol stations and the like. Penelitian ini mengkaji efektivitas layanan self-service bahan bakar di SPBU Stasiun Pertamina Rawa Makmur, Kota Bengkulu, menggunakan analisis bibliometrik. Layanan self-service dirancang untuk meningkatkan efisiensi dan kepuasan pelanggan dalam proses pengisian bahan bakar. Melalui analisis bibliometrik, penelitian ini mengidentifikasi tren penelitian terkini dan hasil evaluasi dari studi-studi terkait implementasi teknologi self-service. Data diperoleh dari publikasi ilmiah, laporan industri, dan studi kasus. Hasil menunjukkan bahwa penerapan self-service dapat mengurangi waktu tunggu dan meningkatkan kepuasan pelanggan, meskipun tantangan seperti adaptasi teknologi dan pelatihan pengTemuan ini memberikan wawasan berharga untuk pengembangan layanan di industri bahan bakar, terutama dalam konteks lokal. Penelitian ini diharapkan dapat memandu strategi peningkatan layanan di SPBU dan sejenisnya.